2019
DOI: 10.17586/2220-8054-2019-10-4-428-437
|View full text |Cite
|
Sign up to set email alerts
|

The minimum size of oxide nanocrystals: phenomenological thermodynamic vs crystal-chemical approaches

Abstract: The minimum crystallite size in a group of oxides has been analyzed as a function of their synthesis conditions, critical nucleus size and the crystal structure parameters. Nanocrystals were synthesized by solution combustion, hydrothermal synthesis and heat treatment in air of the precipitated hydroxides. Aluminum and iron oxides, titania and zirconia, cobalt ferrite, AFeO 3 ferrites (A = Bi, RE), Aurivillius phases Bi m+1 Ti 3 Fe m−3 O 3m+3 (m = 3 -9), as well as solid solutions based on these phases were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…In some cases, it has been shown that the use of additional heat treatment of solution combustion products and other chemical precursors leads to the formation of metastable forms of REE orthoferrites and a significant change in the functional characteristics of materials based on them [231,311,312]. It has been shown that in this case, the chemical and structural background of the precursor exposed to thermal action plays an important role [313][314][315][316], while for other systems, for example, KNO 3 -BaTiO 3 -based ferroelectrics, the necessary properties can be achieved by simple mechanical mixing of the components and the background does not play a significant role [317]. Among the oxide magnetic materials that are promising for use in personalized energy devices, it is also worth noting substances with a spinel structure -Li 0.5 Fe 2.5 O 4 , NiFe 2 O 4 , ZnFe 2 O 4 and others synthesized by solution combustion, successive ionic layer deposition (SILD) (Fig.…”
Section: Features Of the Implementation Of The Combustion Methods Of Gel-like Media In High-speed Kinetic Modementioning
confidence: 99%
“…In some cases, it has been shown that the use of additional heat treatment of solution combustion products and other chemical precursors leads to the formation of metastable forms of REE orthoferrites and a significant change in the functional characteristics of materials based on them [231,311,312]. It has been shown that in this case, the chemical and structural background of the precursor exposed to thermal action plays an important role [313][314][315][316], while for other systems, for example, KNO 3 -BaTiO 3 -based ferroelectrics, the necessary properties can be achieved by simple mechanical mixing of the components and the background does not play a significant role [317]. Among the oxide magnetic materials that are promising for use in personalized energy devices, it is also worth noting substances with a spinel structure -Li 0.5 Fe 2.5 O 4 , NiFe 2 O 4 , ZnFe 2 O 4 and others synthesized by solution combustion, successive ionic layer deposition (SILD) (Fig.…”
Section: Features Of the Implementation Of The Combustion Methods Of Gel-like Media In High-speed Kinetic Modementioning
confidence: 99%
“…The formation of metastable t-ZrO 2 during crystallization and its further polymorphic transformation into m-ZrO 2 is explained by the structural similarity of a-ZrO 2 and t-ZrO 2 [17], and the achievement of the critical crystallite size of about 30 nm, previously obtained [18] based on thermodynamic considerations about the influence of surface energy, respectively. However, the critical size of the t-ZrO 2 crystallite depends on the conditions of synthesis, and subsequent processing of ZrO 2 and can be much less than 30 nm [19] samples that differ in the duration of hydrolysis and heat-treated at 450 -500 • C (Table 2). The imposition of the kinetic factor proposed in [20], namely, only a part of the crystallites with a size above a critical value pass into a new phase, explain the observed decrease in d t .…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…For the synthesis of the samples, the method of the gel combustion was chosen [12,13], the advantages of which are largely associated with the short duration of the high-temperature stage of decomposition of the gel-like precursor, which contributes to the relatively rapid formation of the crystalline phase, hinders the formation of undesirable impurities and makes it possible to obtain nanosized polycrystalline powder materials [17][18][19][20][21]. Nitrates of the yttrium, cerium, iron, gallium and polyvinyl alcohol (PVA) were used as starting reagents for the preparation of Y 3−x Ce x (Fe 1−y Ga y ) 5 O 12 garnets.…”
Section: Introductionmentioning
confidence: 99%